Solidaritas Sosial Antar Pedagang Kaki Lima di Taman Batu 10 Kota Tanjungpinang - Bagus Prasetiyo, Endri; Putra, Ardi; Setia Darmawan, Awan; Husni, Alfi; Anissa Putri, Vika (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
Relationships that can strengthen fellow individuals or groups require a sense of togetherness that arises in the soul of each individual so that a moral bond is formed between each individual. Street vendors are traders who mostly sell by using the roadside area. With the number of traders in Taman Batu 10 as many as 30 people, including 22 men and 8 women, the street vendors also have different ethnicities, namely Javanese, Minangkabau, Sundanese and Malay. One manifestation of this form of street vendor solidarity is providing assistance to assist with buying and selling transactions if one of the traders is going to perform prayers or has a momentary need. In the Taman Batu 10 PKL community there is a structure, namely chairman, deputy chairman, treasurer and secretary. This research method was qualitative by interviewing 10 street vendors. The results of this research show that the solidarity that exists between street vendors in Taman Batu 10 is more dominant in organic solidarity than mechanical. Organic solidarity is a structured division of labor, where the street vendor community in Taman Batu 10 has a management structure which includes a chairman, deputy chairman, secretary and treasurer. In giving punishment or sanctions it is restitutive, namely providing sanctions in the form of returning the situation to its original state. If there is a problem within the Taman Batu 10 PKL community, it will be resolved through deliberation. The feeling of dependency is high as street vendors need other traders to help them lend small money.